Multimedia Courseware for Teaching Arabic Vocabulary: Let’s Learn from the Experts - Zainuddin, Nurkhamimi; Sahrir, Muhammad Sabri (Horizon Research Publishing, USA, 2016)
This study attempts to analyze and evaluate theories and design principles for the design and development of multimedia program for teaching and learning Arabic vocabulary among non-native speakers. In this paper, the researchers mentioned about the research tools, sampling technique and steps as well as population which are related to the design and development process of multimedia courseware which were conducted among the experts in the subject matters (SME). The study proposes the implementation theories of social constructivism by Vygotsky (1978), second language acquisition by Krashen (1984), multimedia learning by Mayer (2001) and ADDIE instructional model by Dick & Carey (1990). The feedbacks were gathered from various SME experts in teaching Arabic as a second language (TASL) and instructional design (ID) who have participated in the study. This paper has concluded the initial theories of design and development of multimedia learning courseware as proposed by the SMEs as outcome of this paper that can be used by the researcher in the design and development processes of related multimedia learning courseware in language learning.